Evaluating the relationship between the requirements of teleworking government establishments with the success of teleworking program in Fars province - Kamyar, Foroogh; Saketi, Parviz (Ciência e Natura, 2015)
Methodology / Approach: To identify the relationship between parameters of teleworking and its success rate in the governmental agencies of Fars province. Population and Statistical Sample: All the inspectors in the Bureau of Labor and Social Affairs, that include 21 members from the operator information “118”, 50 members from the Fars province Telecommunications ministry, with and a total population of teleworkers of n=71 were studied in this research, of which 20 inspectors from the of Fars province and 30 operators information office enquiries “118”, therefore a total n=50 completed the Teleworking questionnaires. Purpose of this study: To evaluate the relationship between the dependent variable (success teleworking) and 5 independent variables (1.rules and regulations 2. the support of Top management 3. perceived benefits of teleworking 4. Trust 5. Culture). Analysis: Descriptive and inferential statistics were carried out, including Pearson correlation, linear regression and multistage regression. Conclusion: The results of this study clearly show that compliance with the Constraints and limitations had a direct and significant impact on the success of teleworking. An interesting point, in this study, is that the simultaneous linear regression model results indicate a significant relationship at relatively high level (69%) between requirements of each of the variables with the success of telework. The results of multiple regression indicate that with regards to the simultaneous effects of the variables consisting of 1.Top management supported 2. Trust 3, Rules and Regulations, 4.Culture, there was a significant correlation with successful teleworking. However, the perceived benefits variable was not significant in the model, and as such the simultaneous effect the cycle was removed. In the information age, with the fast development of systems technologies and telecommunications, a telework program is not just a likely option but a clever and strategic business decision.